Gender differences in business performance: Evidence from the characteristics of business owners survey - Robert W. Fairlie; Alicia M. Robb (University of California, Economics Department, 2009)
Using confidential microdata from the U.S. Census Bureau, we investigate the performance of female-owned businesses, making comparisons to male-owned businesses. Using regression estimates and a decomposition technique, we explore the role that human capital, especially through prior work experience, and financial capital play in contributing to why female-owned businesses have lower survival rates, profits, employment and sales. We find that female-owned businesses are less successful than male-owned businesses because they have less startup capital, less business human capital acquired through prior work experience in a similar business, and less prior work experience in a family business. We also find some evidence that female business owners work fewer hours and may have different preferences for the goals of their businesses, which may have implications for business outcomes.
Keywords: J15; L26; 330; female entrepreneurship; business outcomes; Weibliche Führungskräfte; Entrepreneurship-Ansatz; Unternehmenserfolg; Berufserfahrung; Risikokapital; Vergleich; Männer; USA